Alpha-Synuclein Continues to Enhance SNARE-Dependent Vesicle Docking at Exorbitant Concentrations - Hawk, Brenden J. D.; Khounlo, Ryan; Shin, Yeon-Kyun (Frontiers in Neuroscience, 2019)
Recently, Parkinson’s disease-associated α-synuclein (αS) has emerged as an important regulator for SNARE-dependent vesicle fusion. However, it is controversial if excessive accumulation of αS, even in the absence of aggregation, impairs neurotransmission. Here we use a single vesicle fusion assay with ms time resolution capable of dissecting the impact of αS on each step of membrane fusion. Unlike the previous results from various in vitro, cellular, and in vivo studies, we find that non-aggregated αS promotes vesicle merger even at exorbitant concentrations. The enhancement has been seen as much as 13 fold. Delving into the kinetics of the intermediate states for vesicle fusion reveals that αS stimulates vesicle docking without altering the dynamics of bilayer merger (lipid mixing). However, minute amounts of soluble aggregated species abolish SNARE-dependent bilayer merger completely. Thus, the results show that excessive accumulation of non-aggregated αS may not be toxic for neurotransmitter release.